Public Space as an Urban Acupuncture: Learning From Bandung, Indonesia - Romi Bramantyo Margono; Siswanti Zuraida (Institut Teknologi Sains Bandung, 2019)
Bandung is the capital city of West Java, Indonesia. Since colonial era, Bandung has been designed by Dutch colonizer as tuinstad (garden city) to increase quality of life in this city. It is shown by at least five city garden and several plein (square) built from 1885 to 1925. After colony era, Bandung had been developed, it was also affecting the condition of city garden and squares. It became fenced city parks and squares because of maintenance issue and misconception by local municipality. After decades of degradation of parks and squares, in 2013 new mayor of Bandung Ridwan Kamil, has a vision to bring back again the glory of parks. He believes by revitalizing the parks will increase the quality of life in Bandung and also index of happiness. The parks and squares revitalized by giving specific theme, for example: Superhero Park, Photography Park, Pet Park and so forth. The idea is to attract more people come to park. It is also targeted specific community according to the theme to be part of actor that will maintain the park. The aim of this paper is to describe some critical review of the revitalization of parks in Bandung. In comparison with urban acupuncture concept and also review the quality of the parks and squares as public space.